Journalism and ethics breakthroughs in research and practice (Information Science Reference, 2019)
"This book examines the impacts of journalism on society and the media's responsibility to accurately inform citizens of government and non-government activities in an ethical manner. It also provides emerging research on multimedia journalism across various platforms and formats using digital technologies"--Provided by publisher.